2017
DOI: 10.17998/jlc.17.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Conventional versus Drug-eluting Beads Trans-arterial Chemoembolization for Treatment of Hepatocellular Carcinoma at Very Early and Early Stages

Abstract: Background/Aims: To retrospectively compare conventional and drug-eluting beads transarterial chemoembolization (C-TACE and DEB-TACE) for treatment of hepatocellular carcinoma (HCC) at very early and early stages. Methods:We retrospectively compared patients treated with C-TACE (n=115) or DEB-TACE (n=103) from September 2009 to May 2016. All patients were in a very early (stage 0) or early stage (stage A) of the Barcelona Clinic Liver Cancer (BCLC) staging system, and all had Child-Pugh class A and ≤B7 liver s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Other studies have reported that cTACE could provide similar OS and PFS rates compared to RFA in patients with single small (≤ 3 cm, ≤ 2 cm, and 2–3 cm) HCC. 9 10 11 Although the findings of these previous studies were similar to the OS findings in this study, the previous studies were limited to cTACE.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Other studies have reported that cTACE could provide similar OS and PFS rates compared to RFA in patients with single small (≤ 3 cm, ≤ 2 cm, and 2–3 cm) HCC. 9 10 11 Although the findings of these previous studies were similar to the OS findings in this study, the previous studies were limited to cTACE.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the long-term OS was not statistically significantly different between the RFA and DEB-TACE groups, which may be because additional treatments such as TACE were actively performed for recurrent HCC in both treatment groups. Although several previous studies have compared the long-term survival and treatment responses of cTACE and RFA as first-line treatments in patients with single HCC measuring ≤ 3 cm, 9 10 11 little is known about the survival benefit of DEB-TACE in patients with single small HCC as an initial treatment compared to RFA. Hsu et al 12 compared the OS among patients with HCC treated with cTACE or RFA as an initial treatment and reported that the RFA group had a significantly better long-term OS than the cTACE group before PS matching, but that there was no significant difference in long-term OS after PS matching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, adverse events after SACE were similar to previous studies 24,[33][34][35] , and no serious events (grade 3 or higher) were reported. Additionally, no biliary complications or abscesses were noted.…”
Section: In a Previous Prospective Study Comparing Sace And Conventio...supporting
confidence: 83%
“… 20 , 21 In previous retrospective comparative study of conventional vs. DEB-TACE for small HCC, DEB-TACE provided more procedural safety than conventional TACE and tumor responses between two groups were not significantly different. 22 However, as the authors revealed as a study limitation, the study focused on early-term data at 1 year.…”
Section: Discussionmentioning
confidence: 99%